The influence of assessment for learning, assessment as learning, and assessment of learning on speaking and writing skills in elementary school project-based learning - Slamet, St Y; Winarni, Retno; Syawaludin, Ahmad; Widiarto, Tri; Fakhrudin, Ali (Edelweiss Applied Science and Technology, 2024)
The implementation of project-based learning needs to be supported by knowledge of various assessment models that can influence students’ speaking and writing skills in elementary schools. This research aims to investigate the influence of Assessment for Learning, Assessment as Learning, and Assessment of Learning on speaking and writing skills in project-based learning in elementary schools. This research used a quasi-experimental design with a research sample of 90 students. Data was collected through tests and statistically analyzed by multivariate analysis of variance. The results show that there is a significant influence of the assessment model on students’ speaking and writing skills in elementary schools. The research conclusion is that the assessment model has a significantly different influence on speaking and writing skills. Assessment for Learning obtained the highest results compared to other assessment models. This research provides an overview of selecting and implementing the most effective assessment model for elementary school students’ language skills through project-based learning.